THE IMPACT OF PALM OIL PRICE FLUCTUATIONS ON FARMERS’ WELFARE: A STUDY IN GUNUNG MELAYU VILLAGE - Faradila, Annisa; Putra, Ilham Mirzaya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Selling prices play a crucial role in the lives of oil palm farmers, as the income derived from palm oil is a key factor influencing their welfare. This study aims to examine the impact of changes in the selling price of palm oil on farmers’ welfare, including aspects of health, education, and the economy, as well as the strategies implemented by farmers to cope with the negative effects of palm oil price fluctuations. This research is descriptive in nature and employs a qualitative approach conducted in Gunung Melayu Village, Rahuning Subdistrict, Asahan Regency. Data collection methods include interviews, observation, and documentation. Data analysis in this study is conducted through data reduction, data presentation, and conclusion drawing. The validity of the data is ensured through source triangulation. The results show that the impact of price changes on health includes problems related to family diet and nutrition, such as the inability to consume meals with proper nutritional standards (the four healthy five perfect food concept), the inability to afford medical treatment from doctors or midwives, and only being able to purchase over-the-counter medicine from small shops due to lower prices. In terms of education, families are delayed in paying school fees for two months and eliminate expenditures for non-essential child needs. Furthermore, in the economic aspect, there is an impact on basic family needs, such as reducing grocery shopping from once every three days to once a week, and replacing daily purchases of fish with cheaper alternatives like eggs and instant noodles. Therefore, farmers apply various strategies when facing the negative impacts of palm oil price fluctuations to maintain household income stability, including reducing non-essential expenses, managing family finances wisely, acquiring assets when prices are stable, and seeking side jobs to increase household income.